IFNy+ and IFNy- Treg subsets with stable and unstable Foxp3 expression in kidney transplant recipients with good long-term graft function. - Trojan, Karina; Unterrainer, Christian; Aly, Mostafa Gaafa; Zhu, Li; Morath, Christian; Opelz, Gerhard; Daniel, Volker (Transplant immunology, 2016)
Abstract: Treg are a heterogenous cell population. In the present study we attempted to identify Treg subsets that might contribute to stable and good...